2021
DOI: 10.1080/16549716.2021.1927328
|View full text |Cite
|
Sign up to set email alerts
|

Development of water insecurity scale for rural households in Cameroon- Central Africa

Abstract: Background : Water represents the core of food-energy nexus and is vital for human survival. In developing countries, contaminated water and lack of basic water services undermine efforts to improve nutritional status and related health issues. In the rural areas of Central Africa, a majority of the population lacks access to improved water sources and has to devote considerable efforts to obtain water. Objectives : Using the following definition of water insecurity, i.e. it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…It was also noted that, due to limited water, the use of toilet facilities was avoided, since cleaning them required water. A positive correlation has also been found between limited water access in water insecurity and handwashing ( 13 , 36 ). In the interventions, information on the use of handwashing stations or the frequency of handwashing among intervention households was not collected to determine whether water access is associated with the use of handwashing stations among caretakers.…”
Section: Discussionmentioning
confidence: 94%
“…It was also noted that, due to limited water, the use of toilet facilities was avoided, since cleaning them required water. A positive correlation has also been found between limited water access in water insecurity and handwashing ( 13 , 36 ). In the interventions, information on the use of handwashing stations or the frequency of handwashing among intervention households was not collected to determine whether water access is associated with the use of handwashing stations among caretakers.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the review of other integrated interventions, we concluded that first and foremost W of WASH needs to be addressed. Changes in hygiene behavior and the prevention of cross-contamination cannot be expected until households are water secure or have access to the sufficient amount of clean water at all times (Nounkeu & Dharod 2021). For instance, in the development of household level, water insecurity scale in Cameroon called WATINE-17, it was found that the use of water for household activities, including cooking and daily intake of water, decreased when 'W' was limited (Nounkeu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the review of other small-scale WASH plus nutrition interventions, the modest level of reduction in the diarrhea rate was observed, but no significant joint effect was noted in children's growth. In this review, the complexity and interconnection among various WASH components and nutrition were recognized, and it was highlighted that improvement in the infrastructure at the community level is critical to see WASHrelated health improvement at the household and individual levels (Nounkeu & Dharod 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to water security, insecurity refers to when access to adequate amount of safe and clean water does not occur all the times for the entirety of household members to lead a healthy and active life [17]. To measure water insecurity, the UN developed standards based on per capita water availability and translating equitable and sufficient access to water: (1) per capita daily water use �50 liters; (2) total water collection time �30 minutes; (3) water source � 1,000 meters of home, and; (4) water cost �5% of the household income [18].…”
Section: Plos Watermentioning
confidence: 99%